العولمة: المفهوم، الموقف الإسلامي، وآليات المواجهة : Globalisation: The Concept, The Islamic Perspective, and Mechanisms for Confrontation - دكتور حيات الله (Al Manhal Research Journal, 2025)
This study examines the phenomenon of globalization as one of the most prominent contemporary challenges facing the Islamic world. It analyzes the concept of globalization linguistically and terminologically, and reviews key definitions proposed by Western and Arab scholars. The study distinguishes between two concepts: "universalism" (al-ʿālamiyyah), which Islam advocates as a message of mercy and coexistence, and "globalization" (al-ʿawlamah), which seeks cultural, economic, and political hegemony. The research clarifies that Islam does not reject cultural diversity or interaction with others, provided such interaction adheres to the principles of Islamic law (Sharia). The study also highlights that forced cultural unification contradicts the divine law of human diversity as stated in the Quran. Furthermore, the paper presents a strategic vision for dealing with globalization, emphasizing the importance of fortifying Islamic identity, reforming educational curricula, investing in youth, and promoting the values of moderation and moral integrity. The study concludes that the strength of the Islamic nation lies in its ability to engage with global changes without losing its core identity and values.